Using Six Sigma to improve complaints handling - Abreu, Patrícia (2012)
Currently, companies are in increasingly competitive environment in which customers’ satisfaction and loyalty are vital factors in the success of any organisation. This requires the use of continuous improvement methodologies, such as Six Sigma, which enable companies to improve customer satisfaction and meet their expectations. This paper describes a case study carried out in a company from the automotive industry that has selected a Six Sigma project to respond to a decrease in customer satisfaction regarding the response time of the complaints. The objective of the project was to improve the process of analysis of defective products through the identification of the variables that influence the process and proposes improvements to reduce the time of analysis to defective products. Results are positive and can encourage managers from other industry sectors or even services to improve their customer complaints handling process using Six Sigma.